Central nervous system complications after liver transplantation: Common but mostly transient phenomena. Issue 2 (February 2015) - Bernhardt, Martina; Pflugrad, Henning; Goldbecker, Annemarie; Barg‐Hock, Hannelore; Knitsch, Wolfgang; Klempnauer, Jürgen; Strassburg, Christian P.; Hecker, Hartmut; Weissenborn, Karin; Blanka Tryc, Anita
<x xml:space="preserve">Abstract</x> Although central nervous system complications (CNSCs) are common after orthotopic liver transplantation (OLT), standardized prospective studies are still lacking. This prospective study was aimed at determining the incidence of CNSCs, describing their clinical presentations, and establishing predicting factors. One hundred thirty‐six adult patients who underwent OLT at Hannover Medical School between December 2008 and June 2011 were included. Weekly examinations were performed by a neurologist during the hospital stay after OLT. Patient data, donor data, and operative and postoperative variables were collected. Patients with cerebral dysfunction after OLT underwent a diagnostic work‐up, which included brain imaging and, if necessary, cerebrospinal fluid analysis. Patients with central nervous system (CNS) symptoms but negative imaging and cerebrospinal fluid results and patients with pontine myelinolysis or posterior reversible encephalopathy syndrome were placed in a metabolic‐toxic CNSC group, and patients with strokes, intracranial hemorrhaging, or CNS infections were placed in a nonmetabolic CNSC group. Multiple regression analysis was used to identify independent risk factors for the development of metabolic‐toxic CNSCs. After excluding two patients that died after OLT without regaining consciousness, forty‐four (32.8%) patients developed CNSCs: 37 of these patients (27.6%) had metabolic‐toxic CNSCs, and 7 (5.2%) had nonmetabolic CNSCs. Acute‐on‐chronic liver failure, the number of subsequent surgeries, and primary sclerosing cholangitis were identified as independent predictors for the development of metabolic‐toxic CNSCs. Metabolic‐toxic CNSCs were associated with prolonged hospital stays, and nonmetabolic CNSCs were associated with higher mortality. In conclusion, CNSCs are common and relevant complications after OLT. Patients after OLT, especially with risk factors, should undergo a regular standardized neurological examination that would allow early detection of these complications. Liver Transpl 21:224‐232, 2015. © 2014 AASLD.